Cabo Verde : Technical Assistance Report-Government Finance Statistics and Public Sector Debt Statistics. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2021)
A technical assistance (TA) mission on Government Finance Statistics (GFS) and Public Sector Debt Statistics (PSDS) visited the city of Praia, Republic of Cabo Verde, from July 22 to August 2, 2019, with the aim of putting more and better-quality fiscal data -particularly on PSDS - in the hands of public decision makers. The mission was funded by the Data for Decisions (D4D) fund under module 1 on fiscal data including debt.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Cabo Verde